Professional culture in the context of future veterinarians training - Stukalo, Olena; Стукало, Олена Анатоліївна (Національний педагогічний університет імені М.П. Драгоманова, 2021)
The article is devoted to the problem of forming the professional culture of future veterinarians in the process of their professional training in the system of higher education. The essence of professional culture of future veterinarians and its importance for effective implementation of professional functions are substantiated. It is established that the formation of professional culture of future veterinarians is the result of their professional training, which has a certain content, forms and methods of educational activities. It is proved that the formation of professional culture of future veterinarians is a purposeful process that involves the impact on the student's personality. This effect is carried out in an integrated way through the motivational, cognitive, active sleep spheres of future veterinarians. Стаття присвячена проблемі формування професійної культури майбутніх ветеринарів у процесі їхньої фахової підготовки в системі вищої освіти. Обґрунтовано сутність професійної культури майбутніх ветеринарів і її значення для ефективної реалізації професійних функцій. Встановлено, що сформованість професійної культури майбутніх ветеринарів є результатом їхньої фахової підготовки, що має визначений зміст, форми і методи навчальної діяльності. Доведено, що формування професійної культури майбутніх ветеринарів є цілеспрямованим процесом, що передбачає вплив на особистість студента. Означений вплив здійснюється інтегровано через мотиваційну, когнітивну, діяльнісну сфери майбутніх ветеринарів.
Професійна культура в контексті підготовки майбутніх ветеринарів
Keywords: future veterinarians; майбутні ветеринари; culture; культура; professional culture; професійна культура; professional skill; професійна майстерність; professional training; професійна підготовка